An Analysis of Lexical Collocation Errors in Students’ Writing - I Gede Widi Harta; Indri Wirahmi Bay; Sri Widyarti Ali (TRANS-KATA: Journal of Language, Literature, Culture and Education, 2021)
Mastering lexical collocation uses in learning English as a foreign language is absolutely essential to develop students’ communicative skills and linguistic abilities. Most students, however, have problems with putting words together in a characteristic of “natural” English native speaker-like manner during writing. Students tend to use strange lexical collocation expressions therefore students’ language production does not sound natural and carries imprecise meaning. With regard to this underlying issue, the main emphasis of the current study was lying on the investigation of the types and the causes of lexical collocation error committed by EFL students in their argumentative writing. Through a qualitative research approach applying a descriptive-analytic method, sixteen university students were chosen purposively. The data were collected from two principal sources i.e., students’ writing samples and semi-structured interviews. In terms of data analysis technique, this study employedan error analysis technique developed by Ellis (1994) to analyze the obtained lexical collocation errors and applied a content analysis technique provided by Kumar (2011) to analyze the interview results. The study revealed 54 erroneousness of lexical collocation production consisting of verb + noun/pronoun (PP), adjective + noun, adverb + adjective, noun + noun, and verb + adverb combination. These errors were caused by a lack of collocation competence, native language influence, the use of synonym, overgeneralization, and approximation.